2021
DOI: 10.1111/tri.13978
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of serum aspartate transaminase and gamma‐glutamyl transferase in liver deceased donors

Abstract: The impact of aspartate transaminases (AST) and gamma‐glutamyl transferase (GGT) in serum of deceased donors on outcomes after liver transplantation (LT) is unclear. This study aimed to explore the relationship between donor highest AST value or first donor GGT value and graft survival. All consecutive patients who underwent a primary LT in a single center with available donor AST (N = 1253) and GGT value (N = 1152) were included. There was no significant association between donor AST and 90‐day graft survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Previous studies have shown that 7-day AST values were negatively correlated with long-term graft liver function and patient survival in LT. This study also found that the creatinine values of the two groups at 30 days after surgery were 90.2 ± 22.5 µmol/L and 82.2 ± 16.3 µmol/L, respectively, with a significant difference ( P = 0.019); this result is in line with those of other reports [ 24 ]. However, since the results of this study were only for secondary outcomes and the sample size was small, their significance needs to be further verified.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that 7-day AST values were negatively correlated with long-term graft liver function and patient survival in LT. This study also found that the creatinine values of the two groups at 30 days after surgery were 90.2 ± 22.5 µmol/L and 82.2 ± 16.3 µmol/L, respectively, with a significant difference ( P = 0.019); this result is in line with those of other reports [ 24 ]. However, since the results of this study were only for secondary outcomes and the sample size was small, their significance needs to be further verified.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that 7-day AST values were negatively correlated with long-term graft liver function and patient survival in LT. This study also found that the creatinine values of the two groups at 30 days after surgery were 90.2 ± 22.5 µmol/L and 82.2 ± 16.3 µmol/L, respectively, with a signi cant difference (P = 0.019); this result is in line with those of other reports [23] .…”
Section: Discussionsupporting
confidence: 92%
“…29,30 Also, a single-center French study (1438 recipients between 2004 and 2018) found no significant impact of either AST or GGT on 1-y graft survival, whereas ALT was not examined. 31 The present study is the first large, multicenter cohort study outside of the United States that focuses on donor LBTs and outcome.…”
Section: Discussionmentioning
confidence: 99%